2020
DOI: 10.5888/pcd17.200254
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Telehealth for Better Health Across Communities

Abstract: What is already known on this topic? The COVID-19 pandemic has forced many health care institutions to reconsider health care delivery mechanisms. Because of reimbursement restrictions, telehealth has been underutilized. What is added by this report? Capitalizing on existing infrastructure that supports digital connectivity through uptake of telehealth was vital to successfully reimagine safe health care delivery. Removing a critical barrier, reimbursement, supported telehealth. What are the implications for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…Our study results are limited to telehealth use among the subset of older adults who reported using the internet in the previous 30 days. Audio-only telephone-based telehealth communication, which has become common during the COVID-19 emergency [16] was not measured in this study. Despite these limitations, our findings reinforce the relevance of broadband internet as a consequential factor in equitable access to telehealth and suggest possibilities from policies and programs to extend broadband internet availability and affordability [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Our study results are limited to telehealth use among the subset of older adults who reported using the internet in the previous 30 days. Audio-only telephone-based telehealth communication, which has become common during the COVID-19 emergency [16] was not measured in this study. Despite these limitations, our findings reinforce the relevance of broadband internet as a consequential factor in equitable access to telehealth and suggest possibilities from policies and programs to extend broadband internet availability and affordability [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…With the immediate need for remote care due to the COVID-19 pandemic, many TM restrictions have been waived, and health care systems have rapidly modified their practice to include digital technologies (e.g., telephone, video chat) for remote primary care and specialty services, including medication treatment for OUD (MOUD). In recent years and even more so now, in concert with the rapid uptake of TM, many articles and commentaries [ 3 , 4 ] have been advocating for wider and greater use of TM to improve access to health care and have suggested that broad use of TM during the pandemic should be sustained. While increasing access to care through TM for people with OUD, especially in rural areas severely impacted by the opioid crisis is desirable, research on the implementation and effectiveness of TM-based MOUD is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Characteristics of studies. 41,52,54,55,62,69,77,91,102,105,114,117,122] 14 (11.1) April [17,18,21,30,38,42,43,51,53,61,63-65,68,70,73,75,76,81,82,86,87,90,95,100,101,116,125,129,130,138] 31 (24.6) May [13,20,22,24,25,27-29,31,32,34,36,37,40,44,46,48,50,56,58,67,72,78-80,83,84,89,94,96, 99,103,104,108,113,120,124,132,137] 39 (31.0) June[15,16,23,33,35,39,45,47,49,57,59,66,71,74,85,88,93,97,106,107,109,112,123,126,128,131,[133][134][135][136] [16,18,20,25,30,31,36,37,39,41,46,47,49,50,56,58,67,69,70,…”
mentioning
confidence: 99%
“…Characteristics of technologies in the studies. [13-22,25,26,28,30,31,33,34,36-45,47,49-51,54-59,62-64,66-76,78,79,82-89,92,93,96,97, 99-103,105,107-116,118,119] 29,32,35,46,52,53,60,61,65,77,80,90,95,104,106,117] 17 (15.7) Both[20,25,29,34,41,44,45,47,49,51,56,58,61,69,70,73,76,80,81,83,86,[89][90][91][93][94][95]101,[104][105][106][107]114,115,119,120,122,123,[125][126][127][128]131,132,135,136] 46 (58.2) Built for purpose[14-16,18,20,23-26,31,34,37-39,47,50,53,54,57,62-64,67,69-72,74-77,87,90,96,97,100,101,107, 108,111,113,115,117,120,137] [26,29,44,45,52,75,78,81,85,88,89,93-95,103,104,106-109,117-119,121,122,124,126-136,138] 17,20-24,26-33,35,40,42,43,46,49,52,53,55,59-62,65-68,74,76,77,79,81,82,84,8...…”
mentioning
confidence: 99%